Pemanfaatan Modal Mikro bagi Ibu Rumah Tangga Desa Sawotratap melalui Trading Digital - Rahma, Shafa; Zawawi, Zawawi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Technological developments and digitalization have opened up opportunities for housewives (IRT) to participate in financial markets, but require risk adaptation and digital literacy. This study aims to analyze the use of micro-capital as an investment vehicle and digital trading as a learning tool for small-scale fund management among housewives in Sawotratap Village. The research method used a qualitative-descriptive approach through the Community Service (PkM) program with assistance in micro-trading simulation practices supported by PT Trijaya Pratama Futures (TPFX). The results show that using micro-capital under Rp1 million provides a sense of psychological security and helps participants understand the concept of risk and real-world returns. Micro-digital trading has proven effective in fostering financial management discipline through the implementation of stop-loss strategies, although it still faces emotional control challenges such as overtrading. Therefore, a combination of micro-capital and digital trading is necessary to build the risk management capabilities of housewives in the face of inflationary pressures and rising costs of basic necessities.